2019
DOI: 10.7150/ijbs.28235
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear CD44 Mediated by Importin β Participated in Naïve Genes Transcriptional Regulation in C3A-iCSCs

Abstract: CD44 is one of biomarkers of liver cancer stem cells (CSCs). The investigation of mechanism of CD44 translocation helps to uncover new molecular pathways participated in the regulation of various cellular processes in CSCs. In the present study, we observed the translocation of CD44 from cytoplasm to nuclear in the reprogramming process of C3A cells, full-length CD44 presented in the nucleus of liver iCSCs. CD44 was bound with importin β and transportin 1 in liver iCSCs. Inhibition of importin β transport lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Interestingly, IL-8 further increased the mRNA and protein expression of CD44 in CD44 hi IPF MPCs ( Figure 6A ), but exerted only a modest effect on CD44 expression in CD44 lo IPF MPCs. Prior studies indicate that full-length CD44 can transit to the nucleus where it plays a role in cancer stem cell colony formation ( 16 19 ). Therefore, we next examined the effect of IL-8 on CD44 levels in nuclear and cytoplasmic fractions of CD44 hi IPF MPCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, IL-8 further increased the mRNA and protein expression of CD44 in CD44 hi IPF MPCs ( Figure 6A ), but exerted only a modest effect on CD44 expression in CD44 lo IPF MPCs. Prior studies indicate that full-length CD44 can transit to the nucleus where it plays a role in cancer stem cell colony formation ( 16 19 ). Therefore, we next examined the effect of IL-8 on CD44 levels in nuclear and cytoplasmic fractions of CD44 hi IPF MPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicate that these cells have high levels of full-length CD44 within their nucleus. Prior studies have demonstrated that when the CD44 receptor is ligated, full-length CD44 is internalized and transported to the nucleus where it regulates cellular functions ( 16 19 ). We discovered that IL-8 promotes full-length CD44 nuclear accumulation, a process not previously described.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, CD44 depletion suppressed the proliferation of smooth muscle cells in mice as comparison to wild-type controls [14]. It has been evident that CD44 as a surface biomarker of cancer stem cells (CSCs) and a vital regulatory factor of epithelial-mesenchymal transition (EMT) program is involved in the regulation of tumor initiation and development [6,[15][16][17]. Aberrant expression of CD44 and dysregulation of CD44 contribute to tumor formation of multiple cancer entities, including lung cancer [18], hepatocellular carcinoma [19], ovarian cancer [20], glioma [21], papillary thyroid carcinoma [22], head and neck squamous cell carcinoma (HNSCC) [23], astrocytic gliomas [24] and oral squamous cell carcinoma (OSCC) [25].…”
Section: Open Accessmentioning
confidence: 99%
“…It is highly possible that the scenario that takes place in mouse and rabbit ESCs will also occur in hESCs and hiPSCs. Additionally, GBX2 was reported as a naïve pluripotent marker along with KLF4, NANOG and MYC, which drive the transition of EpiSCs to ESCs [24][25][26] . Altogether, this suggests that Gbx2 is an essential pluripotent protein that promotes cell reprogramming and maintains self-renewal.…”
Section: Discussionmentioning
confidence: 99%